Effects of adding an arbuscular mycorrhizal fungi inoculum and of distance to donor sites on plant species recolonization following topsoil removal. Issue 1 (20th August 2015) - Torrez, Vania; Ceulemans, Tobias; Mergeay, Joachim; de Meester, Luc; Honnay, Olivier
Abstract: Questions: Does addition of an arbuscular mycorrhizal fungi (AMF) inoculum increase the short‐term restoration success of nutrient‐poor grassland (NPG) after topsoil removal? Does distance to intact remnant grassland (IRG) patches affect restoration success, and does the effect of inoculum addition depend on distance to IRGs? Location: Meerdaal forest, Oud‐Heverlee, Belgium. Methods: In a topsoil‐removed site of 8.5 ha, where 24 IRG patches (ca. 10% of the area) were kept, 48 plots (1 m 2 ) were established at three distances (5, 10 and 20 m) from the edge of IRG patches. Half of the plots at each distance class were inoculated with a custom‐made AMF inoculum, whereas the remaining plots were used as controls. We recorded plant species abundance in the plots, just before addition of the AMF inoculum and 1 yr after. We used repeated measures ANOVA to test for effects of inoculum addition, distance to IRG patches and their interaction on plant species richness, diversity and plant community similarity between IRG patches and plots. We also evaluated the response of AMF‐dependent plant species, specialist species of NPG and species with specific seed dispersal adaptations. Results: Adding the inoculum positively affected species richness and/or diversity of all plant species, AMF‐dependent species and specialist species. It increased plant community similarity to the IRG patches. Increasing distance from IRG patches had a negative effect on richness and/or diversity of all plant species and specialist species. The positive effect of inoculum addition on richness and/or diversity of all species, AMF‐dependent species and specialist species decreased with increasing distance from IRG patches to the plots, likely indicating priority effects. Conclusions: The application of a custom‐made AMF inoculum increased the short‐term restoration success of NPG after topsoil removal. Dispersal limitation of specialist plant species of NPG, however, likely negatively affected the effect of inoculum addition. Apart from the AMF effect, the reported strongly positive short‐time effect of inoculation was likely due to the high density of IRG patches at the site, and the presence of organic matter and other micro‐organisms in the inoculum. Abstract : Adding a custom‐made AMF‐inoculum positively affected the species richness and/or diversity of all plant species, AMF‐dependent plant species and specialist plant species. However, dispersal limitation negatively affected the richness and/or diversity of all plant species and specialist plant species. As a result, dispersal limitation negatively affected the effect of inoculum addition in distant areas.